Psychosocial assessment of adolescents and young adults in paediatric hospital settings: patient and staff perspectives on implementation of the e-HEEADSSS - Daniel Waller; Sophie Bailey; Elham Zolfaghari; Jane Ho; Daniela Feuerlicht; Kirsty Ross; Katharine Steinbeck (BMC, 2023)
Abstract Background The main causes of morbidity and mortality for adolescents and young adults are preventable and stem from psychosocial and behavioural concerns. Psychosocial assessments can help clinicians to identify and respond holistically to risks and strengths that may impact upon a young person's physical and mental health. Despite broad support at a policy level, the implementation of routine psychosocial screening for young people remains varied in Australian health settings. The current study focused on the pilot implementation of a digital patient-completed psychosocial assessment (the e-HEEADSSS) at the Sydney Children's Hospital Network. The aim of this research was to evaluate patient and staff barriers and facilitators to local implementation. Methods The research used a qualitative descriptive research design. Semi-structured interviews were conducted online with 8 young patients and 8 staff members who had completed or actioned an e-HEEADSSS assessment within the prior 5 weeks. Qualitative coding of interview transcripts was carried out in NVivo 12. The Consolidated Framework for Implementation Research guided the interview framework and qualitative analyses. Results Results demonstrated strong support for the e-HEEADSSS from patients and staff. Key reported facilitators included strong design and functionality, reduced time requirements, greater convenience, improved disclosure, adaptability across settings, greater perceived privacy, improved fidelity, and reduced stigma for young people. The key barriers were related to concerns over available resources, the sustainability and continuity of staff training, perceived availability of clinical pathways for follow-up and referrals, and risks related to off-site completions. Clinicians need to adequately explain the e-HEEADSSS assessment to patients, educate them about it, and make sure that they receive timely feedback on the results. Greater reassurance and education regarding the rigour of confidentiality and data handling procedures is required for patients and staff. Conclusions Our findings indicate that continued work is required to support the integration and sustainability of digital psychosocial assessments for young people at the Sydney Children's Hospital Network. The e-HEEADSSS shows promise as an implementable intervention to achieve this goal. Further research is required to determine the scalability of this intervention across the broader health system.